The Effect of Light Intensity on the Efficiency of Photochemical Energy Conversion through Electron Transfer - Paul Suppan (CHIMIA)
The thermodynamic properties of light have been the subject of debate for many years. The fundamental question of wether light has a thermodynamic entropy has been discussed of theoretical grounds but so far no experimental data have been available to settle the argument one way or the other. Yet the implications of an entropy content of light are far-reaching from the point of view of practical applications (energy conversion) as well as from that of fundamental knowledge: If light has a thermodynamic entropy, then it cannot be converted entirely into electrical or mechanical energy and the conversion efficiency decreases with the intensity of light. – In this paper the basic assumptions of the entropic and non-entropic models of light are briefly reviewed. It is then shown that the photochemical electron transfer reaction which is involved in the quenching of the fluorescence of some oxonine dyes by electron donor aromatic molecules supports the non-entropic model, which means that the entire energy of light is in principle available in the form of chemical free energy (or electrical or mechanical energy) independently of light intensity.